NUSAS Award & Appreciation Night - Francis, Frannelya (UiTM Sarawak, 2018)
This year the NUSAS Award and Appreciation Dinner for Diploma of Nursing (HS110) was organised on 12 May 2018 at the UCSI Hotel, Kuching in conjunction with the International Nurses’ Day celebration. With the theme ‘Nightingale in Secret Garden - Floral’, NUSAS commemorated the history of modern nursing first introduced by Florence Nightingale. The night was mesmerizing with beautiful garden decorations and creative performances in relation to the nursing profession. It was a memorable night for all the recipients of awards and appreciation. Besides celebrating Nurses’ Day, NUSAS also celebrated Mothers’ Day, Educators’ Day, May Birthday Babies and the success of students achieving Grade Point Average (GPA) of 3.50 and above. The winners for the Nursing Brochure Competition were also announced. The dinner was attended by Ketua Pusat Pengajian (KPP), Dr. Abdul Rahman Saili. The other nursing lecturers and assistant lecturers were also awarded with different titles such as ‘The Most Sporting Lecturer’, ‘The Sweetest Lecturer’ and so on. During the dinner, announcement was made on the dissolution of the outgoing NUSAS committee and the new NUSAS committee was welcomed. The dinner ended with group-photo taking. Everyone present enjoyed the well-organised even